Pengaruh Penggunaan Metode Istiqroiyyah dalam Pembelajaran Shorof Bab Fi'il Tsulatsi Mazid Terhadap Siswa Kelas 8 SMPS Daar El-Falah - Syifa Rahmawati; Laras Gita Rhaudea; Linda Mutia Rahmah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Shorof learning among madrasa students has a very vital role in understanding Arabic writing, including the Al-Qur'an which uses this language. This research aims to investigate the effect of using the istiqroiyyah method in learning shorof, especially in the fi'il tsulatsi mazid chapter. In this research, we carried out a series of learning activities involving various istiqroiyyah methodological approaches, such as games, explanations through stories, and writing examples on the blackboard alternately. We involved 8th grade students and female students at a modern Islamic boarding school, who were divided into two groups: the first group received learning using traditional methods, while the second group used the istiqroiyyah method. The focus of this analysis is the development of students' understanding of the discussion of Fi'il Tsulatsi Mazid in Shorof. The research results showed that the group taught using the istiqroiyyah method experienced a significant increase in their understanding of this chapter, as well as motivating them to continue learning better in the future. These findings emphasize the importance of using the istiqroiyyah method in learning shorof fi'il tsulatsi mazid. The pedagogical implications of this research encourage the need for innovative approaches in teaching shorof science to santri. Thus, the results of this research can be the basis for developing a more effective Arabic language curriculum for students.